Anaplastic lymphoma kinase (ALK) gene rearrangement in non-small cell lung cancer (NSCLC): results of a multi-centre ALK-testing - Laffert, Maximilian von; Warth, Arne; Penzel, Roland; Schirmacher, Peter; Jonigk, Danny; Kreipe, Hans; Schildhaus, Hans-Ulrich; Merkelbach-Bruse, Sabine; Büttner, Reinhard; Reu, Simone; Kerler, Rosi; Jung, Andreas; et al. (Lung cancer, 2013)
Background - The reliable identification of non-small cell lung cancers (NSCLC) with chromosomal breaks in the gene of the anaplastic lymphoma kinase (ALK) is crucial for the induction of therapy with ALK-inhibitors. In order to ensure a reliable detection of ALK-breaks by means of fluorescence in situ hybridization (FISH) testing, round robin tests are essential. In preparation of a nation (German)-wide round robin test we initiated a pre-testing phase involving 8 experts in FISH-diagnostics to identify NSCLC cases (n=10) with a pre-tested ALK-status. In addition, ALK immunohistochemistry (IHC) was performed to assess ALK protein expression. - Material and methods - Sections derived from a tissue microarray, each consisting of 3 cores from 10 NSCLC cases, were independently tested for ALK protein expression by IHC and genomic ALK-breaks by FISH involving 8 institutes of pathology. Based on a pre-screening, 5 cases were identified to be clearly ALK-break negative, whereas the remaining 5 cases were ALK-break positive including one case with low percentage (20%) of positive cells. The latter had been additionally tested by RT-PCR. - Results - The 5 unequivocal ALK-break negative NSCLC were almost consistently scored negative by means of FISH and IHC by all 8 experts. Interestingly, 4 of the 5 cases with pre-defined ALK-breaks revealed homogenous FISH results whereas IHC for the detection of ALK protein expression showed heterogeneous results. The remaining case (low number of ALK-break positive cells) was scored negative by 3 experts and positive by the other 5. RT-PCR revealed the expression of an EML4-ALK fusion gene variant 1. - Conclusion - ALK-break negative NSCLC cases revealed concordant homogeneous results by means of FISH and IHC (score 0-1) by all 8 experts. Discordant FISH results were raised in one ALK-break positive case with a low number of affected tumor cells. The remaining 4 ALK-break positive cases revealed concordant FISH data whereas the ALK-IHC revealed very diverse results. The cases with concordant FISH results provide an excellent basis for round robin ALK-FISH testing. As long as standardized ALK-IHC protocols are missing, ALK protein expression cannot by regarded as the method of choice for identification of patients eligible for treatment with ALK inhibitors.